Non-Destructive Test for IC Package With 8D Report - Mazlan, Muhammad Dinie; Hassan, Hasliza (Evolution in Electrical and Electronic Engineering, 2022)
A semiconductor fabrication facility that converts wafers into integrated circuits is known as Integrated Circuit (IC) Fabrication. Since the sizes of IC are reducing, more complicated manufacturing procedures are being developed and more defect and damaged packaging is being generated. Normally, destructive testing damages the chip turning it worthless for further usage. Therefore, the 8D Report by using Non-Destructive Testing (NDT) is one of the industry’s necessary approaches for tackling the IC failure problem. The purpose of NDT is to examine a component in a safe, dependable, and cost-effective way that does not result in equipment damage or production shutdown. 10 sample of IC will be used and only 3 samples of IC failure will be provided with 8D Report. In order to achieve this objective, the methodology was implemented by using an 8D Report and NDT analysis. 10 samples of IC will run with the NDT method which is the Visual Inspection Method, Functionality Test, and Electrical Test. The result of the testing was 3 IC have failure which is IC broken, pin IC broken, leakage condition, short circuit and open circuit. Therefore, the NDT testing by using 8D Report was one of the advantageous methods to identify and prevent the failure without destructing the IC. In the future, the NDT analysis could be run with the equipment NDT Test such as X-Ray, Scanning Acoustic Microscopy (SAM) and other techniques. Besides that, it needs to expand the use of 8D Report in the industry.